Study on Water Purification Effect of Different Plants in Constructed Wetland of South China - YANG Yongmin; SUN Yiting (Renmin Zhujiang)
Constructed wetlands feature low operating costs and investment,no secondary pollution,good landscape effects,and fast results in short construction periods.In the construction of constructed wetlands,plants play an extremely important role in the purification of sewage from wetlands.To screen suitable wetland plants under the climatic conditions in south China,this paper studies the adaptability of plants to low-concentration domestic sewage and determines the purification efficiency of pollutants and the relationship between the activity of root-zone matrix enzymes and purification efficiency.The test results reveal that rushes,river grass,heliconia,and shell ginger are obviously not suitable for the simulated constructed wetland environment irrigated by sewage,while pickerelweed,cattails,calamus,elephant grass,coix,and windmill grass grow fast and have large biomass,which are suitable for planting in sewage environment.Considering indicators such as the adaptability,purification ability,stress resistance,and landscape effect of the tested wetland plants to the sewage environment,it is concluded that the elephant grass,calamus,cattails,coix,windmill grass,calla,philodendrons,Echinodorus Osiris,and pickerelweed are more suitable for the constructed wetland system.There is a significant correlation between the phosphatase activity and urease and the CODCr removal rate of potted plants,and the enzyme activity of the root-zone matrix urease is not significantly correlated with the TN removal rate and TP removal rate of potted plants.